2015
DOI: 10.1002/dta.1893
|View full text |Cite
|
Sign up to set email alerts
|

Analytical detection of trimetazidine produced by metabolic conversion of lomerizine in doping control analysis

Abstract: The identification of trimetazidine in urine samples might result from administration of the permitted drug lomerizine. Laboratories are therefore urged to carefully investigate suspicious cases where trimetazidine is detected. Differentiation of abuse of the banned substance trimetazidine from use of the permitted drug lomerizine would be supported by analysis of the intact drug lomerizine and/or specific metabolites. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The identification of the anti-migraine drug lomerizine as a precursor of trimetazidine ( Figure 5) was reported by Okano et al, alerting athletes, physicians, and predominantly doping control laboratories and anti-doping organizations of the possibility of AAFs concerning trimetazidine caused by the licit use of lomerizine. [129] A means to differentiate the origin of the prohibited metabolic modulator was suggested with monitoring intact lomerizine and its diagnostic metabolite M6 (N-dealkylated lomerizine, Figure 5) in case of trimetazidine confirmatory analyses. The additional information is considered critical for assigning urinary trimetazidine to the illicit use of the prohibited substance or the permitted use of lomerizine.…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%
“…The identification of the anti-migraine drug lomerizine as a precursor of trimetazidine ( Figure 5) was reported by Okano et al, alerting athletes, physicians, and predominantly doping control laboratories and anti-doping organizations of the possibility of AAFs concerning trimetazidine caused by the licit use of lomerizine. [129] A means to differentiate the origin of the prohibited metabolic modulator was suggested with monitoring intact lomerizine and its diagnostic metabolite M6 (N-dealkylated lomerizine, Figure 5) in case of trimetazidine confirmatory analyses. The additional information is considered critical for assigning urinary trimetazidine to the illicit use of the prohibited substance or the permitted use of lomerizine.…”
Section: Hormone and Metabolic Modulatorsmentioning
confidence: 99%
“…In our earlier study, 5 we demonstrated that when trimetazidine is found in urine samples, further analyses concerning the intact drug lomerizine and/or the metabolite bis-(4fluorophenyl)-methylpiperazine (M6) are indicated. In our earlier study, 5 we demonstrated that when trimetazidine is found in urine samples, further analyses concerning the intact drug lomerizine and/or the metabolite bis-(4fluorophenyl)-methylpiperazine (M6) are indicated.…”
Section: Introductionmentioning
confidence: 99%
“…13 Trimetazidine is generally identified by means of liquid chromatography-tandem mass spectrometry (LC-MS/MS) 5,14 and gas chromatography-mass spectrometry (GC-MS). Mass spectrometric analysis has been the preferred technology for the reliable identification of substances in sports drug testing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations